7-Nitro indazole, an inhibitor of nitric oxide synthase, exhibits anti-nociceptive activity in the mouse without increasing blood pressure. - Moore, P. K. (1993)
7-Nitro indazole (7-NI) inhibits mouse cerebellar nitric oxide synthase (NOS) in vitro with an IC50 of 0.47 microM. Following i.p. administration in mice, 7-NI (10-50 mg kg-1) produces dose-related anti-nociception as evidenced by an inhibition of late phase (15-30 min) but not early phase (0-5 min) hindpaw licking time following subplantar injection of formalin (10 microliters, 5% v/v). The ED50 for this effect was 26 mg kg-1 (equivalent to 159.5 mumol kg-1). Similar i.p. administration of 7-NI (20 and 80 mg kg-1) in urethane-anaesthetized mice failed to increase MAP. Thus, 7-NI is a novel inhibitor of NOS which exhibits selectivity for the brain enzyme. Accordingly, 7-NI may be a useful starting point for the development of selective, centrally acting NOS inhibitors devoid of cardiovascular side effects and as a tool to study the central pharmacological effects of nitric oxide (NO).